On high performance of updates within an efficient document retrieval system - Motzkin, D. (Information processing & management, 1994)
This paper introduces fast, dynamic update algorithms for document retrieval systems. The M-B-T file directory structure, which provides an efficient access path for document retrieval, is utilized for the efficient updates. This directory structure was shown to be compatible with current automatic retrieval and query processing techniques, and to have the capability of including weights that are assigned to index terms and other secondary attribute values with no additional cost. Updates are achieved with a high degree of efficiency. It is shown that this structure achieves a better overall performance than inverted files, standard B-trees, and other directory structures.